Prediction of wave dynamics at certain Pahang beaches - Mustapa, Mohd Zaini; Abdul Hadi, Muhammad Salihi (2016)
Coastal wave dynamics along selected beaches of Pahang comprising the areas from Teluk Chempedak to Kuala Pahang is the subject of this study. Beach stations were monitored monthly for a complete 1-year cycle; beginning from February 2012 to February 2013 at 12 corresponding stations established at random intervals. Model simulation implied that the selected domains are classified as transported area, which having more tendencies to become eroded if any disturbance introduced such as development to the area without proper design and planning. Periodically, changes in currents, tides and wave action, however, produced a normal cycle if the virginity of the beach remains unchanged. The necessity of understanding of these factors is high as to maintain the sustainability for both natural and human systems.